Functionalization of Restorative Dental Glass-Ceramics with Bactericidal Properties. (2022) - Baptista, I.O.; Gomes, F.R.; Vieira, S.; Ferreira, S.; Alves, M.F.R.P.; Santos, C.; Fernandes, M.H.F.
Abstract : Purpose/Aim: Clinically, the periodontitis is related with the dental plaque, a biofilm of microorganisms, growth on the gum line and on the tooth interface. Therefore, a strategy to minimize this condition is the functionalization of the dental prosthesis, usually in contact with the gum, with antibacterial properties. The purpose of this study was to investigate the bactericidal potential of some commercial restorative glass-ceramic materials and to functionalize a commercial dental porcelain with antibacterial properties. Materials and Methods: Commercially available restorative glass-ceramics in powder (IPS d.SIGN), or as monolithic (IPS E.max Press e GC Initial LiSi Press) were used as control samples, and characterized by X-ray diffraction (XRD), Rietveld refinement, differential thermal analysis and particle size distribution. The IPS d.SIGN glass-ceramic was selected for functionalization with nanostructured β-AgVO3 that was synthetized by a hydrothermal route, using AgNO3 and NH4 VO3 as precursors, and characterized by XRD and Scanning Electron Microscopy (SEM). The glass-ceramic material was mixed with different percentages (1%, 2%, 4% or 6%wt) of β-AgVO3, uniaxially pressed at 50 MPa, and thermally treated at 900 C for 5 min, as indicated by the manufacturer. The functionalized glass-ceramics was characterized by XRD, Rietveld refinement, SEM, Vickers Hardness and Vickers indentation fracture toughness. The three commercial glass-ceramics, IPS d.SIGN, IPS E.max Press and GC Initial LiSi Press as well as the functionalized samples were evaluated for its bactericidal potential against model bacteria (Escherichia coli and Staphylococcus aureus). Results: The as-received control samples presented leucite (KAlSi2 O6 ) as the only detectable crystalline phase, 62%wt of amorphous phase and a median particle size (D50) of 25.5 m in IPS d.SIGN. The product of the hydrothermal synthesis was characterized as pure needle like shaped β-AgVO3 crystals. The heat-treated control samples still presented KAlSi2 O6 as the only detectable crystalline phase. However, a secondary feldspar (KAlSi3 O8 ) phase could be detected in the functionalized samples, which turns to be the main crystalline phase as a function of the increase in the β-AgVO3 concentration. None of the commercially available samples showed antibacterial activity, but the IPS d.SIGN samples functionalized with 2%wt or more of β-AgVO3 presented a clear inhibition halo, from 12, 70, 3 mm to 15, 50, 1 mm, suggesting bactericidal activity against both model bacteria. Conclusions: Preliminary, in vitro results indicated that the analyzed commercial dental glass ceramics demonstrated no antibacterial activity. Nevertheless, the functionalization of a commercially available veneering glass-ceramic with at least 2%wt of β-AgVO3 can induce bactericidal activity against gram-positive and gram-negative bacteria.